Participação das células Th1, Th2, Th17 e T regulatórias na doença de Jorge Lobo: análise do perfil de expressão gênica nas lesões - Azevedo, Michelle de Campos Soriani [UNESP] (2015)
Jorge Lobo's disease is a chronic disease that affect the skin and subcutaneous tissues, whose etiologic agent is the fungi Lacazia loboi. Depending on localization of lesions, it can be classified as localized, multifocal or disseminated. In respect to immunologic aspects, previous studies show the predominance of Th2 profile in patients, in addition to more frequent TGF-β and IL-10 positive cells in the inflammatory infiltrate present in lesions. However, the increased understanding about T regulatory (Treg) and Th17profiles suggest that other subpopulation of cells can be involved in the immunopathogenesis of Jorge Lobo's disease. Aiming at explaining the immunoregulation caused by these subpopulations, this study had as objective to evaluate the role of Treg, Th1, Th2 and Th17, through mRNA expression. A total of 114 samples [single lesion patients (55), multiple lesion patients (47) and healthy controls (12)] were evaluated by gene expression of targets associated to Th1 (T-bet, IFN-γ), Th2 (GATA3, IL-5, IL-4, IL-13, IL-33), Th17 (IL-17F) and T regulatory (TGF-β1, FoxP3, CTLA4, IKZF2, IL-10) profiles. The results obtained in this study demonstrated significant higher expression of TGF-β1, IL-10, CTLA4, FoxP3, T-bet and IL-17F, and significant lower expression of GATA3 and IL-4 in all patients. Additionally, the expression comparing single lesions (localized form) and multiple lesions (multifocal and disseminated forms) patients showed significant higher levels of TGF-β1 and IL-5, respectively, in single and multiple lesions patients. In summary, the role of the Treg population is associated with inhibition of the antifungal activity, thus modulating mainly the expression of cytokines associated protection against fungal infection, such as IFN-γ and IL-17F